Hypertension in a female nursing staff-pattern of occurrence, diagnosis, and treatment - Estela Maria Motta Lima Leão de Aquino; Lucélia Batista Neves Cunha Magalhães; Maria Jenny Araújo; Maria da Conceição Chagas de Almeida; Jackline Pereira Leto (Arquivos Brasileiros de Cardiologia, 2001)
OBJECTIVE: To report the pattern of occurrence, diagnosis, and treatment of hypertension in a female nursing staff of an emergency hospital. METHODS: We carried out a cross-sectional study that included interviews and blood pressure measurements of 494 nursing professionals at an emergency hospital in the city of Salvador, in the state of Bahia, Brazil. We considered hypertensive all individual with blood pressure > or = 140/90 mmHg or normal pressure if on regular treatment. RESULTS: We found a prevalence of hypertension of 36.4%. Only 18.3% of the individuals ignored their hypertensive condition, and 64.2% admitted not being having regular treatment. Of those individuals who were having treatment, 69.4% had elevated blood pressure on examination. The major reasons for not being on treatment was the occasional elevation of blood pressure (22.2%) and medical counseling (20.0%). CONCLUSION: The results point to the need to introduce hypertension control measures in this occupational group, because of the magnitude of the disease and the potential impact on diffusion of knowledge and measures to control hypertension.